Rapid screening method of glucocorticoid residues in sample-limited cell-cultured meat - Peiwen Yu; Simeng Li; Chen Zhang; Xiaohui Li; Hongping Wang; Fen Jin (Food Research International, 2026)

A novel conformationally constrained RGD-based cyclic peptide targeting integrin αvβ6 protein for antitumor therapeutic applications - Yang Lv; Chunyu Qu; Yue Lei; Hongrui Zhang; Zeyan Jiang; Simeng Zhao; Tingting Li; Xiaodan Wu; Zhiqiang Wang (Chemico-Biological Interactions, 2026)

Disrupting KRAS–AGO2 interaction: a dual-pronged strategy to sensitize chemo-immunotherapy in KRAS-mutated colorectal cancer - Jingyi Xie; Simeng Wang; Juan Liu; Yan Zhang; Haixiao Zhu; Rongrong Cui; Yao Yao; Wei Yu; Peng Hou (Apoptosis, 2026)

Genetic Variants in EMT-Related lncRNAs Modulate the Risk of Colorectal Cancer in the Chinese Population - Simeng Gu; Zhaohui Zhang; Keyi Cheng; Aibuta Yeerken; Sangni Qian; Fanjia Guo; Mingjuan Jin; Kun Chen (Biochemical Genetics, 2026)

Unpacking rural spatial shrinkage in metropolitan fringe of China: A cross-scale human-land relationship perspective in Chedong, Guangzhou - Simeng Li; Ren Yang; Hualou Long; Wen Yang; Chen Zhang (Journal of Rural Studies, 2026)

Cobalt-doped FeOOH/tubular carbon nitride drives peroxymonosulfate activation for rapid sulfadiazine degradation: Non-radical-dominated oxidation pathways - Jiaqi Chang; Simeng Xia; Yishu Cai; Zhou Shi; Haojie Zhang; Lin Deng (Journal of Environmental Chemical Engineering, 2026)

Integrated removal of calcium and magnesium and extraction of lithium from the mamicuo salt lake in tibet using a pyrrole fluoride-β-diketone/TRPO synergistic system - Simeng Yang; Dong Shi; Lianmin Ji; Yuze Zhang; Jinfeng Li; Xiaowu Peng; Shaolei Xie; Hailong Lu; Yong Niu; Lejie Xu; Lijuan Li (Journal of Environmental Chemical Engineering, 2026)

Efficient removal of perchlorate by a quaternary ammonium-functionalized hydrogel: Performance and mechanisms - Yongkang Guo; Simeng Xia; Zhou Shi; Lin Deng; Haojie Zhang (Journal of Environmental Chemical Engineering, 2026)

Microplastics enter strawberry fruit tissues directly through the epidermis - Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Lihui An; Fen Jin (Journal of Hazardous Materials, 2026)

Reduction of As(V)-bearing goethite by dissolved organic matter from arsenic-prone groundwater during the repeated electron shuttling - Xiaojun Feng; Zhengqi Su; Simeng Li; Xiaoxing Ming; Di Zhang; Huaming Guo (Journal of Hazardous Materials, 2026)

Genome-wide identification of oat EIL gene family and analysis of expression patterns under abiotic stress - Xiaodong Guo; Xuanyu Liu; Jiaming Nie; Qidi Zhang; Simeng Cai; Huiyan Liu; Bing Han; Hongbin Zhao (Genetic Resources and Crop Evolution, 2026)

Celastrol delays the progression of hepatocellular carcinoma by suppressing SLC1A5-mediated glutamine dependence - Simeng Xiao; Yun Zhao; Zhiguo Chen; Yangkun Xiong; Dingmei Zhang; Gang Zhou; Cong Zhang (Toxicology and Applied Pharmacology, 2026)

Comprehensive single-cell profiling uncovers TsMHC-II expression predicting response to neoadjuvant immunotherapy in gastric cancer - Zhiyuan Xu; Zhichun Tang; Simeng Hu; Litao Yang; Jingli Xu; Pengfei Yu; Yian Du; Yanqiang Zhang; Jiahui Chen; Xiaoxiao Wu; Siwei Pan; ShengJie Zhang; et al. (Science Bulletin, 2026)

Mo and S Co-doped Cu-BTC as an efficient catalyst for H2O2 activation to eliminate sulfadiazine through a singlet oxygen dominated non-radical pathway - Haonan Shen; Hangjie Chen; Fan Chen; Simeng Xia; Zhou Shi; Lin Deng; Haojie Zhang (Journal of Environmental Chemical Engineering, 2026)

Drug repurposing: a promising drug discovery strategy for the treatment of emerging epidemic infectious disease - Simeng Zhang; Ruiqing Zhang; Lidan Zheng; Yang Liu; Qing Fan; Yingxu Liu; Xiangzhen Ning; Yanmin Zhang; Yadong Chen; Haichun Liu (Molecular Diversity, 2026)

Insights into the phosphate stabilization and removal mechanism enabled by phosphogypsum-fly ash ceramsite - Simeng Gan; Zhaorui Li; Yunkang Zhang; Fei Wang; Xiaofeng Huang; Yixing Ma; Quxiu Dai; Ping Ning; Kai Li; Xin Sun (Process Safety and Environmental Protection, 2026)

Long-term scenarios for climate adaptation of cotton crops in China, considering multidimensional biophysical and socio-economic scenario analysis - Simeng Guo; Fengqi Wu; Yuhan Wang; Jian Wang; Zhenggui Zhang; Zhanlei Pan; Chenxi Chong; Pengcheng Li; Weibin Huang; Guilan Sun; Xin Li; Shuchen Wang; et al. (Journal of Cleaner Production, 2026)

A gas–liquid entrainment scrubber for fine silica dust control in an ore-crushing workshop: Industrial field testing and integrated assessment - Tao Wei; Ruhua Zhu; Bao Zhang; Linling Zhu; Simeng Fan; Huiqing Luo; Zhaoxing Li; Bulong Bu; Zhentao Li; Xiaochuan Li; Fei Gao (Journal of Cleaner Production, 2026)

Differential cannabinoid-like effects, receptor affinity and physiologically based pharmacokinetics of the synthetic cannabinoids 4F-MDMB-BINACA, 4F-MDMB-BICA and 5F-MDMB-PICA in mice: A comparative study - Yawen Xu; Simeng Zhang; Xuesong Shi; Lixin Kuai; Yuanyuan Chen; Kaixi Li; Xiangyu Li; Yanling Qiao; Dan Wang; Cheng Jiang; Peng Xu (Toxicology and Applied Pharmacology, 2025)

The sanitation in restrooms to respiratory health: modelling concentration distribution changes of bioaerosols across buildings with/without semi-open settings - Ting Zhang; Zuming Wang; Simeng Zhang; Yuying Chen; Guiying Li; Taicheng An (Environmental Pollution, 2025)

Cobalt nanocluster-anchored carbon nanofibers for peracetic acid activation: Dual-radical/nonradical pathways toward efficient roxarsone degradation - Simeng Xia; Jiaqi Chang; Yishu Cai; Zhou Shi; Lin Deng; Haojie Zhang (Chemical Engineering Journal, 2025)

Feasibility of planting shrubs in arid areas from a water balance perspective - Chenguang Zhao; Chao Guan; Tengfei Yu; Jiazheng Wang; Huiying Li; Xia Wang; Baojun Zhang; Simeng Kou; Xuejuan Liu; Changming Zhao (Journal of Hydrology, 2025)

Oral administration of large-leaf yellow tea protein-derived oligopeptides alleviates UV-induced skin photoaging through the inhibition of MAPK/AP-1/MMP9 signaling pathway - Ziyi Shen; Simeng Zhou; Yaru Zhang; Yuan Zhang; Hongyan Wang; Daxiang Li; Yijun Wang; Zhongwen Xie; Huifang Ge (Food Research International, 2025)

Biomimetic solar-driven interfacial evaporation system with effective desalination and volatile organic compounds removal performance - Boli Nie; Weiwei Zhang; Yafu Li; Yuhao Li; Yanming Meng; Xi Zhao; Simeng Niu; Yan-Chao Wu; Hui-Jing Li (Chemical Engineering Journal, 2025)

SERS detection of lung cancer-related volatiles in exhaled breath utilizing size controllable Au NC@ZIF-8 core-shell nanoparticles - Zixuan Wang; Wei Ran; Juan Shen; Yuanyuan Cao; Zhongzhong Wang; Simeng Zhang; Rongzhang Hao (Chemical Engineering Journal, 2025)

Surface hydroxyl-driven =FeOFe(II)+ and =FeOH2+ generation on polyphenol-modified ZVI: Mechanistic insights into Cr(VI) and surface passivation layer removal - Shilin Shi; Chi Zhang; Simeng Guo; Lu Yang; Yuwei Pan; Minghua Zhou; Ying Zhang (Journal of Hazardous Materials, 2025)

Efficient degradation of tetracycline via peracetic acid activation using Fe2SiO4: performance and mechanisms study - Haojie Zhang; Yanzhi Tang; Simeng Xia; Hanxuan Zeng; Zhou Shi; Lin Deng (Journal of Environmental Management, 2025)

A transcriptomics-based analysis provides insights into the sex-dependent reproductive toxicity of DEHP in zebrafish (Danio rerio) - Shirui Liu; Simeng Yu; Yankun Huang; Jingyun Zhang; Kai Song; Shenbao Qu; Cixin Li; Aijiang Yang; Xia Hu (Environmental Toxicology and Pharmacology, 2025)

Novel quantitative method of reactive losses of ambient VOCs coupling chemical transport model simulation with receptor measurement - Yao Gu; Baoshuang Liu; Simeng Ma; Zhongwei Luo; Jinqiu Zhang; Danni Liang; Yafei Li; Yufen Zhang; Yinchang Feng (Journal of Hazardous Materials, 2025)

Carbon, nitrogen, and phosphorus ecological stoichiometry in Cenchrus fungigraminus and soil under waterlogging stress - Simeng Song; Hengyu Zhou; Pingxuan Li; Lin Zhang; Dewei Su; Dan Zheng; Zhaoxiong Zhang; Zongzhi Luo; Shikui Yu; Bin Liu; Zhanxi Lin; Dongmei Lin (Plant and Soil, 2025)

Nuclear protein 1 protects against neonatal hypoxic-ischemic encephalopathy by inhibiting neuronal ferroptosis by improving iron storage - Xining He; Simeng Wei; Yunsheng Fu; Hongxia Li; Jie Zhang; Li Liu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Comprehensive insights into oil absorption in fried foods: The role of surface characteristics - Shuangyi Zhang; Zhiguo Gong; Simeng Wang; Shuli Zhao; Wei Mao; Bo Liu; Ying Liu (Food Chemistry, 2025)

Osthole–pyrethrins combination loaded onto hollow microsphere silica nanoparticles inhibits Fusarium solani growth and controls root rot incidence in Cynanchum auriculatum - Xiaomeng Fei; Bing Xie; Junjie Tang; Lixia Wang; Yong Zheng; Haifeng Kuai; Simeng Li; Daoguo Zhang; Wei Gu (Physiological and Molecular Plant Pathology, 2025)

Quantitative source apportionment of surface ozone in Liaoning Province, China, under the Asian summer monsoon background - Ningwei Liu; Simeng Ma; Kun Wang; Sen Yang; Zhigang Zhang (Atmospheric Pollution Research, 2025)

Metabolome genome-wide association analyses identify a splice mutation in AADAT affects lysine degradation in duck skeletal muscle - Dapeng Liu; Wenlei Fan; Youyou Yang; Zhanbao Guo; Yaxi Xu; Jian Hu; Tong Liu; Simeng Yu; He Zhang; Jing Tang; Shuisheng Hou; Zhengkui Zhou (Science China Life Sciences, 2025)

Revealing considerable emissions reduction potential in flight operations: A real-time emission perspective - Simeng Ma; Shizhuo Lin; Bo Han; Chen Zhang; Zhiqiang Wei; Lingxiang Xue; Jingbo Zhao; Kun Wang; Jian Yu; Philip K. Hopke (Transportation Research Part D: Transport and Environment, 2025)

Study on the interventional effect and molecular mechanism of HSP72 in regulating oxidative stress by watermelon seed peptide RDPEER - Ziqi Yan; Simeng Chen; Chidimma Juliet Igbokwe; Yuqing Duan; Kai Hu; Meihong Cai; Haihui Zhang (Food Chemistry, 2025)

Using explainable machine learning to predict the irritation and corrosivity of chemicals on eyes and skin - Yingxu Liu; Yang Liu; Simeng Zhang; Chen Zeng; Qing Zhang; Yunya Jiang; Xi Yang; Lidan Zheng; Qian Ge; Yanmin Zhang; Yadong Chen; Mengyi Lu; et al. (Toxicology Letters, 2025)

Tracing the carbon footprint of cotton garments from seed to garment: Evidence from an empirical study of multiple sites in China - Shuchen Wang; Chenxi Chong; Weibin Huang; Simeng Guo; Yuhan Wang; Yaopeng Zhang; Zhanlei Pan; Jian Wang; Xin Li; Wenqi Zhao; Zhenggui Zhang; Zhanbiao Wang (Resources, Conservation and Recycling, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A Novel COLREGs-Based Automatic Berthing Scheme for Autonomous Surface Vessels - Shouzheng Yuan; Gongwu Sun; Yunqian He; Yuxin Sun; Simeng Song; Wanyuan Zhang; Huifeng Jiao (Journal of Marine Science and Engineering, 2025)
This paper tackles the highly challenging problem of automatic berthing for autonomous surface vessels (ASVs), encompassing trajectory planning, trajectory tracking, and collision avoidance. Firstly, a novel A* algorithm integrated with a quasi-uniform B-spline and quadratic interpolation method (A*QB) is proposed for generating a smooth trajectory from the initial position to the berth, utilizing an offline-generated scaled map. Secondly, the optimal nonlinear model predictive control (NMPC)-based trajectory-tracking framework is established, incorporating the model’s uncertainty, the input saturation, and environmental disturbances, based on a 3-DOF model of a ship. Finally, considering the collision risks during port berthing, a COLREGs-based collision avoidance method is investigated. Consequently, a novel trajectory-tracking and COLREGs-based collision avoidance (TTCCA) scheme is proposed, ensuring that the ASV navigates along the desired trajectory, safely avoids both static and dynamic obstacles, and successfully reaches the berth. To validate the TTCCA approach, numerical simulations are conducted across four scenarios with comparisons to existing methods. The experimental results demonstrate the effectiveness and superiority of the proposed scheme.

Dissipation patterns of trisiloxane ethoxylates in cucumber plants and field soils: Insights from different end-capping groups - Simeng Li; Xiaohui Li; Chen Zhang; Bowen Li; Peiwen Yu; Qin Dai; Hongping Wang; Fen Jin (Journal of Hazardous Materials, 2025)

Enzymatic degradation of Ochratoxin A by a novel bacterium, Microbacterium esteraromaticum ASAG1016 - Ru Jia; Jingyi Zhao; Senmiao Tian; Faizan Ahmed Sadiq; Simeng Lu; Pengyan Gao; Guohua Zhang (International Journal of Food Microbiology, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

A novel polydopamine-loaded copper sulfide (CuS@PDA) for activating H2O2 to eliminate tetracycline via 1O2 dominated oxidation pathway - Zhou Shi; Chenxi He; Hao Huang; Xile Huang; Tong Hu; Yijia He; Dazhi Yang; Simeng Xia; Haojie Zhang; Lin Deng (Journal of Water Process Engineering, 2025)

Drivers of civil aviation emissions in China: Considering spatial heterogeneity and interdependence - Simeng Ma; Wenhui Zheng; Bo Han; Zhiqiang Deng; Jinglei Yu; Jingbo Zhao; Chen Zhang; Jian Yu; Philip K. Hopke (Environmental Pollution, 2025)

Grassland irrigation and grazing prohibition have significantly affected vegetation and microbial diversity by changing soil temperature and moisture, evidences from a 6 years experiment of typical temperate grassland - Xi Lin; Hongbin Zhao; Shengwei Zhang; Qinsi He; Alfredo Huete; Lin Yang; Xiaoduo Zhang; Xiaofu Zhang; Qidi Zhang; Simeng Cai (Agriculture, Ecosystems & Environment, 2025)

Plant polyphenols as natural bioactives for alleviating lipid metabolism disorder: Mechanisms and application challenges - Haiying Wei; Jinsheng Rui; Xinke Yan; Ruyan Xu; Simeng Chen; Baiming Zhang; Lei Wang; Zhisong Zhang; Chengwen Zhu; Mengtao Ma; Huining Xiao (Food Research International, 2025)

Entropy-TOPSIS-based quantitative evaluation of specific roles of the enhanced coagulation process in multi-objective sewage pre-concentration by microfiltration - Yukun Xing; Xiaoxiang Zhang; Simeng Han; Lanxin Ling; Xiyuan Feng; Xiaoyu Zhang; Zhaotong Liu; Zhengyu Jin (Journal of Water Process Engineering, 2025)

Distinctive Neural Substrates of low and high Risky Decision Making: Evidence from the Balloon Analog Risk Task - Zhenlan Jin; Simeng Li; Changan Wang; Xiaoqian Chai; Junjun Zhang; Ling Li (Brain Topography, 2025)

Concentration, pathogenic composition, and exposure risks of bioaerosol in large indoor public environments: A comparative study of urban and suburban areas - Jiasheng Ni; Simin Huang; Zhishu Liang; Zhen Chen; Simeng Zhang; Guiying Li; Taicheng An (Science of The Total Environment, 2024)

Assessing the impact of various irrigation technologies on agricultural production: A water-energy‑carbon nexus perspective - Sifu Liu; Simeng Cui; Jan F. Adamowski; Nan Wu; Mengyang Wu; Pingping Zhang; Xinchun Cao (Science of The Total Environment, 2024)

Lithium extraction from high-Mg brines using N523/esters systems - Lianmin Ji; Dong Shi; Yuze Zhang; Jinfeng Li; Xiaowu Peng; Shaolei Xie; Simeng Yang; Nan Chen; Hailong Lu; Yong Niu; Lijuan Li (Journal of Water Process Engineering, 2024)

Unveiling the critical roles of nascent MnO2 in accelerating permanganate carbocatalysis - Jun Wang; Simeng Bi; Li Wei; Yi Shen; Fanpeng Meng; Yang Zhang; Xiaoyao Tan (Journal of Hazardous Materials, 2024)

Contribution of plastic solid components to volatile organic compounds formation during plastics combustion - Xinglei Wang; Simeng Tang; Ling Ding; Xinran Qiu; Zhenming Zhang; Li Xu; Xujun Liang; Xianfei Huang; Xuetao Guo (Journal of Hazardous Materials, 2024)

The relationship between starch synthesis enzyme activity, gene expression, and amylopectin fine structure in waxy maize - Haiyan Zhang; Fan Qin; Guanghai Xu; Simeng Geng; Yuan Yuan; Ming Wang; Fuchao Jiao; Jingtang Chen (Cereal Research Communications, 2024)

Recent advances on transport and transformation mechanism of nanoplastics in lung cells - Simeng Zhang; Hangxi Zhang; Yichen Li; Zhiwei Sun; Yueyue Chen (Science of The Total Environment, 2024)

Exploring emission spatiotemporal pattern and potential reduction capacity in China's aviation sector: Flight trajectory optimization perspective - Simeng Ma; Xuan Wang; Bo Han; Jingbo Zhao; Zhongyi Guan; Jinlong Wang; Yufen Zhang; Baoshuang Liu; Jian Yu; Yinchang Feng; Philip K. Hopke (Science of The Total Environment, 2024)

High-efficiency electro-Fenton synergistic electrocoagulation for enhanced removal of refractory organic pollutants - Kang Liu; Tao Xu; Simeng Hu; Xiaojie Zhuang; Yihui Zhou; Xiping Lei; Xueyuan Zhang; Lianwu Xie (Journal of Environmental Management, 2024)

In situ grown single-atom cobalt on carbon nanofibers for efficient adsorptive removal of antibiotics: Performance and mechanisms understanding - Simeng Xia; Fan Chen; Zhou Shi; Lin Deng; Anett Georgi; Haojie Zhang (Chemical Engineering Journal, 2024)

An integrated framework for improving green agricultural production sustainability in human-natural systems - Simeng Cui; Jan F. Adamowski; Mengyang Wu; Pingping Zhang; Qiong Yue; Xinchun Cao (Science of The Total Environment, 2024)

Natural variation in photosynthetic electron transport of wheat flag leaves in response to dark-induced senescence - Cheng Yang; Zishan Zhang; Yuan Yuan; Deqi Zhang; Haiyang Jin; Ying Li; Simeng Du; Xiangdong Li; Baoting Fang; Fang Wei; Ge Yan (Journal of Photochemistry and Photobiology B: Biology, 2024)

In situ anchoring of bimetal (Cu, Fe) sulfides featured by sulfur vacancy and phosphorus doping within porous carbon nanocubes derived from Prussian blue analogs to activate peroxymonosulfate for the efficient degradation of organic pollutants - Jiaqi Chang; Simeng Xia; Zhou Shi; Hanxuan Zeng; Haojie Zhang; Lin Deng (Chemical Engineering Journal, 2024)

Exposure to volatile organic compounds and growth indicators in adolescents: Unveiling the association and potential intervention strategies - Jingyi Ren; Xiaoya Sun; Zhenao Zhang; Huanting Pei; Yadong Zhang; Rui Wen; Simeng Qiao; Zidan Wang; Weican Zhang; Jinshi Zuo; Yuxia Ma (Journal of Hazardous Materials, 2024)

One-step rapid removal of Cu(II) complexes via dual-active-site MOF catalysis with Peroxymonosulfate: Cooperative oxidation and adsorption - Shuo Wang; Simeng Guo; Xuedong Du; Ziqian Liu; Yujia Yang; Yaran Song; Qingrui Zhang (Chemical Engineering Journal, 2024)

Risk Factors for Preoperative Cerebral Infarction in Infants with Moyamoya Disease - Qingbao Guo; Songtao Pei; Qian-Nan Wang; Jingjie Li; Cong Han; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; Zhengxing Zou; et al. (Translational Stroke Research, 2024)

The abundance and pathogenicity of microbes in automobile air conditioning filters across the typical cities of China and Europe - Kaifei Su; Zhishu Liang; Simeng Zhang; Wen Liao; Jianwei Gu; Yunlong Guo; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2024)

Automated offset detection approaches: case study in IGS Repro2 and 3 - Jin Zhang; Lizhen Lian; Chengli Huang; Cancan Xu; Simeng Zhang (GPS Solutions, 2024)

Zinc oxide nanoparticles damage the prefrontal lobe in mouse: Behavioral impacts and key mechanisms - Dan Zhang; Zhiyuan Wang; Hongmei Deng; Simeng Yi; Tao Li; Xinjiang Kang; Jun Li; Chang Li; Tingting Wang; Bo Xiang; Guang Li (Toxicology Letters, 2024)

Bee colonies map the short- and medium-chain chlorinated paraffin contamination from the apiary environment - Shujun Dong; Suzhen Qi; Yazhou Zhao; Su Zhang; Xingyi Wu; Jun Cao; Yun Zou; Yuesen Wang; Simeng Xia; Peilong Wang; Liming Wu (Science of The Total Environment, 2024)

Comprehensive sensitivity analysis of the WRF model for meteorological simulations in the Arctic - Tong Zhang; Le Cao; Simeng Li; Chenchao Zhan; Jiandong Wang; Tianliang Zhao (Atmospheric Research, 2024)

Multi-model predictive control strategy for path-following of unmanned surface vehicles in wide-range speed variations - Yingkai Ma; Zhilin Liu; Ting Wang; Simeng Song; Jing Xiang; Xiaoyue Zhang (Ocean Engineering, 2024)

Imidacloprid triggered changes in strawberry fruits on edible quality and phenolic profiles by applied at two growth stages - Ning Yue; Chen Zhang; Simeng Li; Hongping Wang; Xiaohui Li; Xueying Chen; Fen Jin (Food Research International, 2024)

Fuzzy composite risk assessment of water-energy-food-carbon nexus in the dispark pumped irrigation system - Simeng Cui; Jianyun Zhang; Xiaojun Wang; Mengyang Wu; Xinchun Cao (Journal of Hydrology, 2023)

An ultrasensitive and specific ratiometric electrochemical biosensor based on SRCA-CRISPR/Cas12a system for detection of Salmonella in food - Simeng Zheng; Qian Yang; Haoyu Yang; Yunzhe Zhang; Wei Guo; Wei Zhang (Food Control, 2023)

Analysis of differential metabolites and metabolic pathways in adipose tissue of tree shrews (Tupaia belangeri) under gradient cooling acclimation - Dongmin Hou; Huibao Chen; Ting Jia; Lin Zhang; Wenrong Gao; Simeng Chen; Wanlong Zhu (Journal of Thermal Biology, 2023)

Microbiome-metabolomics analysis insight into the effects of dietary resistant starch on intestinal integrity - Simeng Qin; Keying Zhang; Xuemei Ding; Shiping Bai; Jianping Wang; Gang Tian; Yue Xuan; Zhuowei Su; Quifeng Zeng (Food Chemistry, 2023)

Comparative analysis of nitrate evolution patterns during pollution episodes: Method development and results from Tianjin, China - Yafei Li; Yan Han; Simeng Ma; Yufen Zhang; Haoqi Wang; Jingyi Yang; Lu Yao; Xiaohui Bi; Jianhui Wu; Yinchang Feng (Science of The Total Environment, 2023)

Histone modification in podocyte injury of diabetic nephropathy - Simeng Wang; Xinyu Zhang; Qinglian Wang; Rong Wang (Journal of Molecular Medicine, 2022)

Heme oxygenase-1 protects against endotoxin-induced acute lung injury depends on NAD+-mediated mitonuclear communication through PGC1α/PPARγ signaling pathway - Simeng He; Jia Shi; Wenming Liu; Shihan Du; Yuan Zhang; Lirong Gong; Shuan Dong; Xiangyun Li; Qiaoying Gao; Jing Yang; Jianbo Yu (Inflammation Research, 2022)

NEK7: a new target for the treatment of multiple tumors and chronic inflammatory diseases - Jin Wang; Simeng Chen; Min Liu; Min Zhang; Xiaoyi Jia (Inflammopharmacology, 2022)

TMEM92 acts as an immune-resistance and prognostic marker in pancreatic cancer from the perspective of predictive, preventive, and personalized medicine - Simeng Zhang; Xing Wan; Mengzhu Lv; Ce Li; Qiaoyun Chu; Guan Wang (EPMA Journal, 2022)

Correction to: Downregulation of fibronectin 1 attenuates ATRA‑induced inhibition of cell migration and invasion in neuroblastoma cells - Xiaolin Tan; Wei Gong; Bo Chen; Baocheng Gong; Zhongyan Hua; Simeng Zhang; Yang Chen; Qi Li; Zhijie Li (Molecular and Cellular Biochemistry, 2022)

Metabolomics changes in brain-gut axis after unpredictable chronic mild stress - Qiuyue Xu; Mingchen Jiang; Simeng Gu; Xunle Zhang; Guangkui Feng; Xianjun Ma; Shijun Xu; Erxi Wu; Jason H Huang; Fushun Wang (Psychopharmacology, 2022)
Background Major depressive disorder is a leading cause of disability worldwide, affecting up to 17 % of the general population. The neural mechanisms of depression, however, are yet to be uncovered. Recently, attention has been drawn to the effects of dysfunctional brain-gut axis on depression, and many substances have been suggested to be involved in the communication between the gut and brain, such as ghrelin. Methods We herein systematically examined the changes of metabolomics after unpredictable chronic mild stress (UCMS)–induced depression-like behaviors in rats and compared the altered metabolites in the hippocampus and jejunum samples. Results Our results show that many metabolites significantly changed with UCMS both in the hippocampus and jejunum, such as L-glutamine, L-tyrosine, hydroxylamine, and 3-phosphoglyceric acid. Further studies suggested that these changes are the reasons for anxiety-like behaviors and depression-like behaviors in UCMS rats and also are the reasons for hippocampal neural plasticity. Conclusions Coexistence of brain and gut metabolic changes in UCMS-induced depressive behavior in rats suggests a possible role of brain-gut axis in depression. This study provides insights into the neurobiology of depression.

Downregulation of fibronectin 1 attenuates ATRA-induced inhibition of cell migration and invasion in neuroblastoma cells - Xiaolin Tan; Wei Gong; Bo Chen; Baocheng Gong; Zhongyan Hua; Simeng Zhang; Yang Chen; Qi Li; Zhijie Li (Molecular and Cellular Biochemistry, 2021)

Factors affecting the soil–water retention curve of Chinese loess - Fanyu Zhang; Chongxi Zhao; Sérgio D. N. Lourenço; Simeng Dong; Yao Jiang (Bulletin of Engineering Geology and the Environment, 2021)

Autophagy May Be Involved in Fluoride-Induced Learning Impairment in Rats - Chengzhi Zhang; Simeng Huo; Yumei Fan; Yanhui Gao; Yanmei Yang; Dianjun Sun (Biological Trace Element Research, 2020)

P53/PUMA are potential targets that mediate the protection of brain-derived neurotrophic factor (BDNF)/TrkB from etoposide-induced cell death in neuroblastoma (NB) - Zhongyan Hua; Yue Zhan; Simeng Zhang; Yudi Dong; Min Jiang; Fei Tan; Zhihui Liu; Carol J. Thiele; Zhijie Li (Apoptosis, 2018)